Calculation of Peak Particle Velocity Caused by Blasting Vibration in Step Topography - Yang, Xi (ITB Journal Publisher, LPPM ITB, 2018)
High ground vibrations not only adversely affect the integrity of the structures in a mine area but also create inconvenience for the nearby population. In order to protect the Sanyou Mine slope in Tangshan, China from blasting vibration, the peak particle velocity in step topography must be accurately calculated. At present, the reflection coefficient of the stress wave at free interface is not considered in the equation for calculating the peak particle velocity in step topography. Therefore the accuracy of the peak particle velocity calculation is decreased in the side direction when the reflection coefficient changes. In this study, a 3D finite element analysis was employed for modeling of the blasting vibration. A series of field-testing experiments was conducted to measure the peak particle velocity. Then the reflection coefficient of the stress wave was calculated. Based on this, the principle of the peak particle velocity in step topography was explained. In addition, the application range of the equation in step topography was determined and a new equation for peak particle velocity calculation in step topography is proposed based on the numerical simulation analysis and field-testing experiment.